FROM PONDS TO MAN-MADE SEAS IN RUSSIA - Sergey Gorshkov; Laurent Touchart; Olga Mochalova; Andrey Ozerskiy; Larissa Evseeva (Geography, Environment, Sustainability)
Russia has more than 2200 reservoirs and large ponds. As time went by, ponds lost their importance in some aspects of human life, while newly created man-made seas impacted the nature and the people in two ways. The costs involved in designing, constructing, and operating the artificial seas, especially on the plains, have been too high to consider them as an undisputed achievement of the Soviet scientists transforming the nature. This paper discusses the problem of ponds and man-made seas in Russia.